Comparison of methods for diagnostics and treatment of clinical manifestations of the papilloma viral infection - M. R. Rakhmatulina; A. V. Semenenko (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article describes modern methods for diagnostics of clinical, subclinical and latent forms of the papilloma viral infection. The authors reviewed different methods of the destruction of anogenital warts and described their advantages and shortcomings. They provide the results of studies of the efficacy of Imiquimod for the treatment of anogenital warts.